Rectification and validation of a daily satellite-derived Antarctic sea ice velocity product - Tian, Tian R.; Fraser, Alexander D.; Kimura, Noriaki; Zhao, Chen; Heil, Petra (The cryosphere, 2022)
Antarctic sea ice kinematics plays a crucial role in shaping the Southern Ocean climate and ecosystems. Satellite passive-microwave-derived sea ice motion data have been used widely for studying sea ice motion and deformation, and they provide daily global coverage at a relatively low spatial resolution (in the order of 60 km × 60 km). In the Arctic, several validated datasets of satellite observations are available and used to study sea ice kinematics, but far fewer validation studies exist for the Antarctic. Here, we compare the widely used passive-microwave-derived Antarctic sea ice motion product by Kimura et al. (2013) with buoy-derived velocities and interpret the effects of satellite observational configuration on the representation of Antarctic sea ice kinematics. We identify two issues in the Kimura et al. (2013) product: (i) errors in two large triangular areas within the eastern Weddell Sea and western Amundsen Sea relating to an error in the input satellite data composite and (ii) a more subtle error relating to invalid assumptions for the average sensing time of each pixel. Upon rectification of these, performance of the daily composite sea ice motion product is found to be a function of latitude, relating to the number of satellite swaths incorporated (more swaths further south as tracks converge) and the heterogeneity of the underlying satellite signal (brightness temperature here). Daily sea ice motion vectors calculated using ascending- and descending-only satellite tracks (with a true ∼ 24 h timescale) are compared with the widely used combined product (ascending and descending tracks combined together, with an inherent ∼ 39 h timescale). This comparison reveals that kinematic parameters derived from the shorter-timescale velocity datasets are higher in magnitude than the combined dataset, indicating a high degree of sensitivity to observation timescale. We conclude that the new generation of “swath-to-swath” (S2S) sea ice velocity datasets, encompassing a range of observational timescales, is necessary to advance future research into sea ice kinematics.